Disability in instrumental activities of daily living among older adults: gender differences - Alexandre, Tiago da Silva; Corona, Ligiana Pires; Nunes, Daniella Pires; Santos, Jair Lício Ferreira; Duarte, Yeda Aparecida de Oliveira; Lebrão, Maria Lúcia (Revista de Saúde Pública, 2014)
OBJECTIVE To analyze gender differences in the incidence and determinants of disability regarding instrumental activities of daily living among older adults. METHODS The data were extracted from the Saúde, Bem-Estar e Envelhecimento (SABE – Health, Wellbeing and Ageing) study. In 2000, 1,034 older adults without difficulty in regarding instrumental activities of daily living were selected. The following characteristics were evaluated at the baseline: sociodemographic and behavioral variables, health status, falls, fractures, hospitalizations, depressive symptoms, cognition, strength, mobility, balance and perception of vision and hearing. Instrumental activities of daily living such as shopping and managing own money and medication, using transportation and using the telephone were reassessed in 2006, with incident cases of disability considered as the outcome. RESULTS The incidence density of disability in instrumental activities of daily living was 44.7/1,000 person/years for women and 25.2/1,000 person/years for men. The incidence rate ratio between women and men was 1.77 (95%CI 1.75;1.80). After controlling for socioeconomic status and clinical conditions, the incidence rate ratio was 1.81 (95%CI 1.77;1.84), demonstrating that women with chronic disease and greater social vulnerability have a greater incidence density of disability in instrumental activities of daily living. The following were determinants of the incidence of disability: age ≥ 80 and worse perception of hearing in both genders; stroke in men; and being aged 70 to 79 in women. Better cognitive performance was a protective factor in both genders and better balance was a protective factor in women. CONCLUSIONS The higher incidence density of disability in older women remained even after controlling for adverse social and clinical conditions. In addition to age, poorer cognitive performance and conditions that adversely affect communication disable both genders. Acute events, such as a stroke, disables elderly men more, whereas early deficits regarding balance disable women more.